Narcissism and Quality of Life: The Mediating Role of Relationship Patterns. Issue 8 (August 2020) - Ellison, William D.; Acuff, M. Chase; Kealy, David; Joyce, Anthony S.; Ogrodniczuk, John S.
Abstract : Abstract: Pathological narcissism is associated with decreased quality of life, even when accounting for psychiatric comorbidity, but the processes behind this association are unclear. Here, we evaluate whether disturbed relatedness accounts for the negative association between narcissistic pathology and quality of life. Patients in day hospital treatment for personality pathology ( N = 218, 70% female; mean age, 37.3 years) completed measures of personality disorder features, quality of life, and global symptoms before beginning treatment. Quality of object relations was assessed through semistructured interviews. Regression-based mediation analyses showed that narcissistic personality traits relate to quality of life through quality of object relations, controlling for other personality disorders and psychiatric distress. These results highlight the importance of problematic relationship patterns for the low quality of life associated with pathological narcissism. Clinicians working with narcissistic individuals should consider psychotherapies that promote mature relatedness and should attend to facilitating the quality of patients' relationships.